Determinants of Argentina's External Trade - Falcetti, Elisabetta; Catao, Luis. (Washington, D.C. : International Monetary Fund, 1999)
This paper presents new estimates of export and import equations for Argentina, using a broader set of variables than previous studies and distinguishing between intra- and extra-MERCOSUR trade. It measures the importance of relative price versus income effects in accounting for the higher trade deficit during the 1990s, and examines whether foreign trade elasticities have increased as a result of structural changes in the economy. It finds that the high income elasticity of imports and the responsiveness of exports to changes in world commodity prices, domestic absorption, and economic activity in Brazil have been key determinants of Argentina's trade balance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet